PENGARUH FITUR TARIK TUNAI TANPA KARTU DAN FITUR QRIS PADA MOBILE BANKING BANK SYARIAH INDONESIA TERHADAP EFISIENSI BERTRANSAKSI NASABAH STUDI PADA MAHASISWA PERBANKAN SYARIAH ANGKATAN TAHUN 2021-2023 - Rika Akana Putri; Fatana Suastrini (Nusantara Hasana Journal, 2025)
In Bank Syariah Indonesia's mobile banking service, technological innovations such as cardless cash withdrawal features and QRIS have been introduced to improve service quality and make customer transactions easier. This research aims to analyze the influence of these two features on customer transaction efficiency. This research uses quantitative methods by involving Sharia Banking students from the Class of 2021–2023 at FEBI UIN Mataram as respondents. Data was collected through an online questionnaire and analyzed using multiple linear regression. The research results show that the cardless cash withdrawal feature (X1) and the QRIS feature (X2) have a positive and significant influence on transaction efficiency (Y). Based on the partial hypothesis test (t test), the calculated t-value was 3.938 for X1 and 10.066 for In addition, simultaneously, these two features have a significant impact on transaction efficiency, as shown by the results of the coefficient of determination test. The coefficient of determination obtained is 0.848, indicating that 84.8% of the variability in transaction efficiency can be explained by the cardless cash withdrawal feature and the QRIS feature. Thus, these two features play an important role in increasing the efficiency of customer transactions.